Synthesis and antibacterial evaluation of nitrogen containing novel heterocyclic chalcones. Issue 11 (3rd June 2018) - Kaushik, Reena; Chand, Mahesh; Jain, Subhash C.
ABSTRACT: Thirteen different novel heterocyclic chalcones were synthesized using cycloaddition and Claisen–Schmidt condensation reactions. These newly synthesized compounds were characterized by their spectral studies and structure of ( E )-3-(4-methoxyphenyl)-1-(5-methyl-1-(pyridin-3-yl)-1 H -1, 2, 3-triazol-4-yl)prop-2-en-1-one (4h ) was also evidenced by single crystal X-ray studies. These compounds were evaluated for antibacterial activities against seven bacterial strains in vitro . Compounds4b and4c containing 4-fluoro and 4-chloro groups have shown remarkable inhibition as showed by the standard drug ciprofloxacin against Escherichia coli and Staphylococcus aureus, respectively. Another compound4k containing 3, 4, 5-trimethoxy group also showed similar activity against both these strains. Beside these three potential compounds4b, 4c, 4k, one more compound4g containing 4-methyl group showed equivalent inhibition as that of standard drug against E. coli. These categories of compounds are therefore good candidates for developing new effective antibacterial in future. GRAPHICAL ABSTRACT: